London youth, religion, and Politics : Engagement and Activism from Brixton to Brick Lane - Dehanas, Daniel Nilsson (United Kingdom Oxford University Press, 2016)
This study concerns the role of religion in the civic integration of London's second-generation youth through comparative ethnographic studies of two groups: the predominantly Christian Jamaican population in Brixton and the predominantly Muslim Bangladeshi population of the East End.
Including Colors Illustration and Index
Keywords: Muslim youth -- Race relations -- Urban youth